Strategi Implementasi Kebijakan Manajemen Peningkatan Mutu Berbasis Sekolah (MPMBS) Pada Sekolah Menengah Pertama - Abdul Tolib (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2015)
This article aims to describe Implementation Strategy of School-Based Quality Improvement Management In Junior High School in Indramayu. The findings of this study indicate that: first, the state of education at Junior High School in Indramayu different from each other. Among the schools there is a gradation sequence, especially in the quality of educational output produced. Secondly, in formulating policy, the principal invited the participation of all school component of school stakeholders, but not all stakeholders participating policies that had been developed then neatly documented in various forms of school documents. policies that have been set together and then disseminated in various forums both formal and informal, such as through meetings, briefings, and everyday conversation. Third, in general all schools have developed a pattern of quality improvement based management school. Quality improvement activities carried out through the process of planning, implementation, monitoring and evaluation. However. Management’s ability to improve the quality of the different schools with other schools.